Categorizing and translating abbreviations and acronyms - Imre Attila (Open Linguistics, 2022)
The popularity of various types of abbreviations makes it necessary to rediscuss their categorization and possible disambiguation. We rely on categorization types applied in cognitive linguistics, also confronting definitions and forms stemming from both linguistic and software-based approaches. A major distinction is observed between abbreviations resulting from one-word and multi-word sequences, leading to various subtypes with prototypical, less central, and hybrid cases. Although guidelines offer advice on their use, these rules should be re-evaluated in specific settings, such as subtitling and translation. While previous research on the topic focused on journal articles, we have collected a database of nearly 13,000 abbreviations and acronyms from five American TV series with the help of a specially designed algorithm. Our research also highlights the importance of punctuation, exemplifying some of the most frequent ones with alternative versions (with or without period) and discusses the Romanian and Hungarian translations of a well-known American agency. The concluding remarks mention that even if subtitle conventions are not severely regulated, a database of acronyms may significantly improve quality, especially in the case of TV series.